EFFORTS TO INCREASE STUDENTS READING INTEREST THROUGH THE MULTIMEDIA-BASED GLENN DOMAN LEARNING MODEL IN CLASS II SD RAMEUAN STATE DISTRICT LIKE MAKMUE REGENCY KINGDOM NAGAN - Aslami, Rozatul; Fahreza, Febry; Kistian, Agus (International Journal of Students Education, 2023)
This study aims to increase students’ interest in reading through the Glenn Doman learning model based on multimedia in class II at SD Negeri Rameuan, Suka Makmue District, Nagan Raya Regency. This research is a Classroom Action Research (PTK), which is carried out in two cycles consisting of planning, implementation, action, observation, and reflection. This type of research is qualitative research. In this study, there were 25 students in class II of SD Negeri Rameuan. Collecting research data through teacher observation sheets, student observation sheets, documentation, and questionnaires. All students of grade II SD Negeri Rameuan with a total of 25 students, 15 students could not read. Based on the results of the study it is known that there has been an increase using the Multimedia-Based Glenn Doman learning model. The results of student observations in accordance with observations in cycle I obtained a percentage value of 74.3% in the good category, the results of teacher observations obtained a percentage value of 82.14% in the good category and the results of the questionnaire obtained a value of 63.5% in the fairly good category. The results of student observations in accordance with observations in cycle II obtained a score of 95% in the very good category. The results of teacher observations obtained a score of 100% in the very good category and the results of the questionnaire obtained a value of 93.9% in the very good category. Thus it can be concluded that the use of the Multimedia- Based Glenn Doman learning model can increase students’ interest in reading in class II of SD Negeri Rameuan, Suka Makmue District, Nagan Raya Regency. the results of teacher observations obtained a percentage value of 82.14% in the good category and the results of the questionnaire obtained a value of 63.5% in the fairly good category. The results of student observations in accordance with observations in cycle II obtained a score of 95% in the very good category. The results of teacher observations obtained a score of 100% in the very good category and the results of the questionnaire obtained a value of 93.9% in the very good category.